PEMBEKALAN PELATIHAN KERJA DALAM MENUMBUHKAN MINAT USAHA BAGI NARAPIDANA DI LAPAS - Maharidho Deel Ziko; Ali Muhammad (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2022)
Abstract The increase in criminal activities occurring in the community has led to an increase in the population of the Institute (LAPAS). The government, as the policymaker in this case, advises prisoners so prisoners do not commit crimes again and are motivated. Work The purpose of this study was to analyze the effect of entrepreneurship training and work motivation on entrepreneurial interest in prisons. Data collection techniques with literature, observation and interviews. The program observed by researchers is an entrepreneurship education program in the form of skills training and direct communication. The tool used for data collection is the interview form. The results of this study indicate that there is a significant impact of entrepreneurship training and 100% motivation on entrepreneurial interest. This means that entrepreneurship training and better motivation for this Work are carried out by inmates, entrepreneurial interest will increase and vice versa.